SUNSET POLICY UNTUK WAJIB PAJAK BERDASARKAN PASAL 37 A UNDANG UNDANG KETENTUAN UMUM PERPAJAKAN - KRISTIANTO, DJOKO (Universitas Slamet Riyadi, 2009)
Abstract: Sunset policy is a government program to invite people to pay their tax. Sunset policy is hoped to improve structure and infra structure tax paying. Sunset policy aims at driving tax payer in fulfilling their obligation. The opportunity to the tax payer to become the honest tax payer trough this policy is hoped to raise tax paying in the future. This willing in paying tax need to be conducted by giving an easy service and transparent management. Therefore, it is necessary to explain the society about the rules and the related laws. It is hoped to give improvement in tax paying. Keywords: sunset policy, tax payers, obidience